The Exploration of Chlorophyll Content of Various Plants in City Forest of Malabar Malang - Roimil Latifa; Samsun Hadi; Endrik Nurrohman (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2019)
Abstract This current research aimed at investigating chlorophyll content of various plants growing in the city forest of Malabar Malang. Descriptive quantitative method was employed as the research design. This research was conducted from April to August 2019 in city forest of Malabar and Biology Laboratory University of Muhammadiyah Malang. The data were analyzed by means of Microsoft Excel. There were three steps of the research, as follows: a) surveying the research location; b) taking samples of each leaf; and c) laboratory testing. Laboratory testing comprised some stages, as below: a) weighing each leaf sample at 0.3 gram, grounded and dissolved in 80% acetone; b) filtering by utilizing filter paper, and c) testing by means of spectrophotometer with the wavelengths of 645λ and 663λ, respectively to result in absorbance value. The results of absorbance value were tabulated into a specific formula to find out the content of chlorophyll a, chlorophyll b, and the total chlorophyll of each leaf sample. This current research has revealed that regarding the average scores, chlorophyll a has been found the highest in Averrhoa bilimbi leaf (35.848 µg/ml) and the lowest is in Averrhoa carambola leaf (17.857 µg/ml). The average score of chlorophyll b has been found the highest in Tabebuya leaf (58.862 µg/ml) and the lowest is in nortflok pine leaf (9.124 µg/ml). As for the total average of chlorophyll content, the highest content was extracted from Tabebuya leaf (91.737 µg/ml), and the lowest is found in nortflok pine leaf (28.517 µg/ml).